Analysis of Poverty Convergence at The District/City Level in East Java Province - Harun Al Azies; Wahyu Wisnu Wardana (East Java Economic Journal, 2020)
This paper aims to investigate the presence of poverty convergence across regions in East Java over the period of 2008-2018. By employing ?-convergence dan ?-convergence, we find that in general there is no strong evidence of poverty convergence across regions. Furthermore, disaggregating the analysis into urban (city) and rural (municipality) areas reveals that there is a tendency of poverty convergence across cities in East Java. In contrast, the finding suggests that municipalities in East Java tended to experience poverty divergence. Other conclusions based on the results of absolute and conditional convergence show that there is a process of convergence of poverty in urban (city) and rural (municipality) during the period 2011-2014.